Scaling of Advanced Theory-of-Mind Tasks - Osterhaus, Christopher; Koerber, Susanne; Sodian, Beate (Child development, 2016)
Advanced theory-of-mind (AToM) development was investigated in three separate studies involving 82, 466, and 402 elementary school children (8-, 9-, and 10-year-olds). Rasch and factor analyses assessed whether common conceptual development underlies higher-order false-belief understanding, social understanding, emotion recognition, and perspective-taking abilities. The results refuted a unidimensional scale and revealed three distinct AToM factors: social reasoning, reasoning about ambiguity, and recognizing transgressions of social norms. Developmental progressions emerged for the two reasoning factors but not for recognizing transgressions of social norms. Both social factors were significantly related to inhibition, whereas language development only predicted performance on social reasoning. These findings suggest that AToM comprises multiple abilities, which are subject to distinct cognitive influences. Importantly, only two AToM factors involve conceptual development.